Interfacial Assembly of Mussel‐Inspired Au@Ag@ Polydopamine Core–Shell Nanoparticles for Recyclable Nanocatalysts. (8th November 2013) - Zhou, Jiajing; Duan, Bo; Fang, Zheng; Song, Jibin; Wang, Chenxu; Messersmith, Phillip B.; Duan, Hongwei
<x xml:space="preserve">Abstract</x> Recyclable nanocatalysts of core–shell bimetallic nanocrystals are developed through polydopamine coating‐directed one‐step seeded growth, interfacial assembly, and substrate‐immobilization of Au@Ag core–shell nanocrystals. This strategy provides new opportunities to design and optimize heterogeneous nanocatalysts with tailored size, morphology, chemical configuration, and supporting substrates for metal‐catalyzed reactions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>